Choose the correct simplification of (3x + 5y)(4x - 3y).

Question

Asked 7/25/2013 3:29:31 AM

Updated 3/30/2015 11:08:58 PM

2 Answers/Comments

Question

Asked 7/25/2013 3:29:31 AM

Updated 3/30/2015 11:08:58 PM

2 Answers/Comments

Rating

3

(a^5b)(a^2b) = a^7b^2

Added 6/28/2014 8:38:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/30/2015 11:09:06 PM]

3

(3x + 5y)(4x- 3y)

=(3x)(4x) + (3x)( - 3y) + (5y)(4x) + (5y)( - 3y)

=12x^2 - 9xy + 20xy - 15y^2

=12x^2 + 11xy - 15y^2

=(3x)(4x) + (3x)( - 3y) + (5y)(4x) + (5y)( - 3y)

=12x^2 - 9xy + 20xy - 15y^2

=12x^2 + 11xy - 15y^2

Added 3/30/2015 11:08:58 PM

This answer has been confirmed as correct and helpful.

27,094,575

questions answered

There are no comments.